When tourism refreshes memories: geopolitical acts, geopolitics in action - Isabelle Lefort; Dominique Chevalier (Via@)
This article offers an analysis of memorial tourism from a geopolitical perspective. An initial focus on the invention and implementation of this type of tourism in various contexts leads to the realisation that it is doubly geopolitical: in the memories that it mobilises and the historic moments that render it (more or less) acceptable. This type of tourism is an operator of memories and, in parallel, an actant of geopolitical relations. An analysis of the devices and the actual practices of memorial tourism leads finally to a discussion of the reception of the messages conveyed by the dedicated structures.